O processo de recupera????o de falhas no varejo e a influ??ncia da justi??a nos antecedentes da lealdade dos consumidores - Silva, Marcos Antonio da (2011)
The retail sector has an important role in the national economic composition. According to the Brazilian Institute of Geography and Statistics (IBGE), in 2008 the sector moved R $ 576 billion in net revenue, representing 39.6% of all revenue generated by the commercial sector. This substantial performance by retailers is directly related to service delivery and to the maintenance of relationships with customers as a tool for differentiation and business continuity. The scale of many retail operations creates a need for failure recovery plans, intended to recover and maintain consumer loyalty. Given that consumers view the resolutions of their claims in different ways and form judgments of these resolutions that influence the continuity of their relationships with retailers, this research proposes to study the process of failure recovery in retail and the influence of justice in the history of consumer loyalty. The study collected information from consumers who have been through a real process of failure recovery, to construct a theoretical model that was then analyzed through structural equation modeling and through the technique of partial least squares (PLS). The theoretical framework that was used encompassed relationship marketing and recognized antecedents of consumer loyalty. The results demonstrated understanding on the part of consumers in their judgments of the results of the failure recovery process and, primarily, a positive influence in their assessment of their satisfaction as an important aspect for building loyalty to the supplier